The Invisible Mustahik: Exploring Social Exclusion and Barriers to Zakat Access for Prostitutes in Yogyakarta's Digital Space - Furqonul Haq; Athira Salsabila (Sharia Economic and Management Business Journal (SEMBJ), 2025)
This study aims to analyze the social exclusion of 11 digital prostitutes in Yogyakarta as "Invisible Mustahik" through the theoretical framework of social exclusion by Amartya Sen and Hilary Silver. This research is significant in filling the gap in the literature on Islamic philanthropy for stigmatized groups, by examining how administrative barriers and moral stigma hinder their access to zakat. This qualitative research used a netnographic design in the digital space MiChat Yogyakarta, involving 11 prostitutes selected through purposive sampling for primary data collection. The data were then analyzed thematically using an analysis similar to ATLAS.ti software to examine the correlation between administrative barriers, moral stigma, and typologies of social exclusion. This research identifies six typologies of "Invisible Mustahik," characterized by vulnerability driven by a lack of local identity and social stigma. These barriers significantly restrict 11 sex workers' access to the zakat system, thereby depriving them of their capabilities as asnaf. This study recommends that zakat institutions relax domicile administrative requirements and develop anonymous and stigma-free digital outreach protocols. These findings are crucial for policymakers transforming the Islamic philanthropy system to be more inclusive of hidden populations in the digital space. This research makes a unique contribution by introducing the concept of "Invisible Mustahik" to the hidden population in the MiChat app, a niche rarely explored in Islamic philanthropy literature. Its novelty lies in the synthesis of Sen's Capability Theory and Silver's Exclusion Paradigm to reconstruct the asnaf criteria to be more inclusive of marginalized groups in the digital space.